2020
DOI: 10.3390/ani10081359
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Outcomes and Endocrine Profile in Artificially Inseminated versus Embryo Transferred Cows

Abstract: The increasing use of in vitro embryo production (IVP) followed by embryo transfer (ET), alongside with cryopreservation of embryos, has risen concerns regarding the possible altered pregnancy rates, calving or even neonatal mortality. One of the hypotheses for these alterations is the current culture conditions of the IVP. In an attempt to better mimic the physiological milieu, embryos were produced with female reproductive fluids (RF) as supplements to culture medium, and another group of embryos were supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Accurate selection of competent in vitro produced (IVP) embryos for transfer to recipients is essential to maximize pregnancy and birth rates. Currently, the selection of viable IVP embryos is based on morphology and development stage, subjective criteria that rarely allow birth rates over 45% with either fresh or cryopreserved embryos [ 1 , 2 , 3 , 4 , 5 ]. The interest in identifying reliable markers of embryonic viability is higher in IVP, and mainly with respect to cryopreserved embryos, because of their intrinsic reduced viability to term.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate selection of competent in vitro produced (IVP) embryos for transfer to recipients is essential to maximize pregnancy and birth rates. Currently, the selection of viable IVP embryos is based on morphology and development stage, subjective criteria that rarely allow birth rates over 45% with either fresh or cryopreserved embryos [ 1 , 2 , 3 , 4 , 5 ]. The interest in identifying reliable markers of embryonic viability is higher in IVP, and mainly with respect to cryopreserved embryos, because of their intrinsic reduced viability to term.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Pimenta-Oliveira et al [ 29 ], found differences in birth weight of the offspring between the IVP embryos and AI. Nonetheless, Lopes et al [ 30 ], compared the growth of calves born by ET with those from AI, and their results showed much similarity between groups in terms of pregnancy rates, gestation length and calves’ birth weight. In our study, male calves recorded higher birth weights than females.…”
Section: Discussionmentioning
confidence: 99%
“…Using sex-sorted semen for artificial insemination of in vitro fertilization enables livestock producers to preserve or increase their herds without having to purchase additional females or exposing the herd to potential pathogens and diseases [ 71 , 72 , 73 ]. Additionally, the use of sex-sorted semen in conjunction with other reproductive biotechnologies has the potential of improving the global livestock management by allowing for the predetermination of an animal’s sex, thus maximizing the profitability of farms [ 74 , 75 , 76 , 77 , 78 ].…”
Section: Conventional and Sex-sorted Semen Market—present And Future Trendsmentioning
confidence: 99%